2021
DOI: 10.3389/fneur.2021.687697
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Effect of Erenumab on Efficacy and Quality-of-Life Parameters in a Cohort of Migraine Patients With Treatment Failure in Cyprus

Abstract: Erenumab is the first human monoclonal antibody to be approved as a selective therapy for migraine prophylaxis in adults. This study assessed, in a real-world setting, the efficacy of erenumab and its impact on the quality of life (QoL) of Cypriot migraine patients who had failed several treatments in the past. Erenumab was prescribed as a stand-alone or as an add-on therapy to 16 patients with chronic migraine. The first component of the study examined migraine parameters before and after erenumab therapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Emerging literature on patients with migraine treated with erenumab and other CGRP monoclonal antibodies outside of clinical trials has demonstrated improved outcomes for a significant proportion of cases [ 17 20 ]. We audited 17–30 months of PROM/QoL data in our cohort of treatment/medically resistant or difficult to treat CM patients to give us insight into the more medium to long-term benefits of anti-CGRP intervention in this type of patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging literature on patients with migraine treated with erenumab and other CGRP monoclonal antibodies outside of clinical trials has demonstrated improved outcomes for a significant proportion of cases [ 17 20 ]. We audited 17–30 months of PROM/QoL data in our cohort of treatment/medically resistant or difficult to treat CM patients to give us insight into the more medium to long-term benefits of anti-CGRP intervention in this type of patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging literature on patients with migraine treated with erenumab and other CGRP monoclonal antibodies outside of clinical trials has demonstrated improved outcomes for a significant proportion of cases [17][18][19][20]. We Persistence with preventive treatments in migraine in the medium to long term (1-3 years) is a good combined measure of efficacy and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the difficulty of access, and despite the small number of participants, it was still possible to robustly demonstrate the expected effects. In favor of this argument, other research types have been published with sample sizes similar to the present study (76)(77)(78). On the other hand, social adaptation was also considered through the protocol study that considered inclusion criteria associated with a population normally adapted to daily life.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational cohort study assessing the effect of erenumab on efficacy and quality of life parameters (mental well-being, anxiety, and depression levels) examined with the validated Migraine-Specific Quality-of-Life Questionnaire—Version 2.1 (MSQ V2.1) concluded that in the 3-month-interval treatment period, 81.3% of the patients reported an improvement in the examined parameters [ 85 ].…”
Section: Recommended Prophylactic Treatment Options In CMmentioning
confidence: 99%